2017
DOI: 10.1136/bmjoq-2017-000106
|View full text |Cite
|
Sign up to set email alerts
|

Improving the workflow of nursing assistants at a general hospital in Japan

Abstract: Transferring non-specialised tasks from registered nurses to nursing assistants may help registered nurses focus on specialised tasks. Optimising the workflow of nursing assistants by making their tasks more efficient may improve problems associated with the shortage of registered nurses. The nursing assistants at our hospital were stressed about referring inpatients to outpatient specialty clinics. Therefore, we initiated a project to optimise the referral process and reduce the time spent by nursing assistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…We developed TEAMS-BP at the University of Tsukuba in 2012 with the co-operation of the Japan Industrial Training Association (Maeno 2016;Isono et al 2017). It is based on the Japanese Training Within Industry-Job Method (TWI-JM) (Graupp and Wrona 2006).…”
Section: Process Improvement Designmentioning
confidence: 99%
See 3 more Smart Citations
“…We developed TEAMS-BP at the University of Tsukuba in 2012 with the co-operation of the Japan Industrial Training Association (Maeno 2016;Isono et al 2017). It is based on the Japanese Training Within Industry-Job Method (TWI-JM) (Graupp and Wrona 2006).…”
Section: Process Improvement Designmentioning
confidence: 99%
“…Further analysis of individual cases is required to identify the steps during which the delays occur and why they happen. A previous study of nursing assistants showed that an advantage of TEAMS-BP is its ability to elicit improvement by repeating the four-step cycle, and that improvements will continue to be made (Isono et al 2017).…”
Section: Further Improvementsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study conducted in Cameroon reported that the flowchart is a decision-making and vocational training tool. A good technique for handling flowcharts, observed in 10/16 nurses, is associated with their systematic initial use and with the standardization of care [4]. However, the inadequate reading skills of dichotomous trees hinder their application in the diagnostic decisionmaking.…”
Section: Introductionmentioning
confidence: 99%